Rotational thromboelastometry (ROTEM®)-guided diagnosis and management of amniotic fluid embolism. (May 2019) - Loughran, J.A.; Kitchen, T.L.; Sindhakar, S.; Ashraf, M.; Awad, M.; Kealaher, E.J.
Highlights: Amniotic fluid embolism is a rare obstetric emergency with high mortality. Diagnosis is by exclusion of other causes of maternal collapse. Laboratory tests taking up to 90 min are not useful to aid real time diagnosis. Point-of-care testing could be useful in both diagnosis and management. Point-of-care testing can help guide individualized blood product management. Abstract: Amniotic fluid embolism is a rare but often catastrophic emergency. The non-specific clinical features and lack of diagnostic tests make it a diagnosis of exclusion. Point-of-care visco-elastometric testing is being increasingly used during obstetric haemorrhage. We present a case of amniotic fluid embolism, diagnosed and managed using rotational thromboelastography. During a precipitous labour, a 21-year-old multiparous woman became pale, distressed and disorientated. The fetus was delivered using forceps. Simultaneously maternal cardiac arrest occurred and advanced life support was commenced. As there was no obvious bleeding, pulmonary embolism was considered the most likely diagnosis and preparation was made to thrombolyse. During resuscitation, rotational thromboelastometry demonstrated haemostatic failure, supporting a diagnosis of amniotic fluid embolism. This reversed the decision to thrombolyse and focused the team on resuscitation and management of coagulopathy. Targeted blood products were given using a local protocol specific to obstetric bleeding. Return of cardiac output was achieved. The total measured blood loss was more than 3.6 L and transfusion was guided by point-of-care tests. Transfused blood products were six units of packed red blood cells, one pool of platelets, 12 units of fresh frozen plasma and 14 g of fibrinogen concentrate. This case demonstrates amniotic fluid embolism with haemostatic failure, without initial revealed blood loss. The high mortality of amniotic fluid embolism necessitates rapid diagnosis and aggressive management. Laboratory tests in this context are impractical in informing clinical decisions, showing the value of point-of-care testing in facilitating team work and timely administration of targeted blood products.